Steane Code Analysis by Randomized Benchmarking - Barbosa, Anderson de Souza; Marquezino, Franklin de Lima; Portugal, Renato (Proceedings of the Theory of Computation Meeting (ETC), 2022)
Randomized Benchmarking (RB) is a protocol that allows to partially characterize the quality of the implementation of a set of quantum gates. In this work, we use the RB protocol to analyze the performance of the Steane code, an important quantum error correction code, and we present a scenario in which its use is advantageous when compared to the situation in which no quantum code is used.